Conversion of placental alkaline phosphatase from a phosphatidylinositol-glycan-anchored protein to an integral transmembrane protein. - Berger, J (1989)
Placental alkaline phosphatase (PLAP) is normally anchored to the plasma membrane of cells by a phosphatidylinositol-glycan anchor after removal of a carboxyl-terminal peptide from the nascent enzyme. To investigate the signals required for this processing we constructed a chimeric cDNA. The latter was designed to code for a truncated precursor form of PLAP, containing the phosphatidylinositol-glycan attachment site but incapable of any form of membrane attachment, fused to a carboxyl-terminal peptide of vesicular stomatis virus glycoprotein. Expression of the PLAP-vesicular stomatis virus glycoprotein chimeric cDNA in transfected COS cells produced an enzymatically active protein that was attached to the plasma membrane, with the PLAP domain on the outer surface. Assays for the presence of phosphatidylinositol-glycan attachment proved negative, whereas an antibody assay confirmed the presence of the vesicular stomatis virus glycoprotein carboxyl-terminal peptide, leading to the conclusion that the truncated PLAP is attached to the cells by the membrane-spanning domain of the vesicular stomatis virus glycoprotein. In light of previous findings on carboxyl-terminal requirements of PLAP these studies suggest that an essential signal for correct sorting between transmembrane insertion and phosphatidylinositol-glycan attachment resides in the cytoplasmic domain.